2023
DOI: 10.1186/s12883-023-03189-4
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the level of stigma and the factors influencing it in the rehabilitation of young and middle-aged stroke patients-a cross-sectional study

Abstract: Background There are few reported studies on stigma in young and middle-aged stroke patients during the rehabilitation period, however, the rehabilitation period plays a key role in the patients’ disease regression. Exploring the level of stigma and the influencing factors in young and middle-aged stroke patients during the rehabilitation period is crucial for determining how to reduce the level of stigma and improve the patients’ motivation for rehabilitation treatment. Therefore, this study i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Second, this study confirms that stigma has a significant positive impact on loneliness, with interpersonal sensitivity playing a partial mediating role between the two. Finally, we find that resilience plays a moderating In this study, the stigma of young and middle-aged stroke survivors was higher than that of participants in the study by Zheng et al (2023). This may attributed to differences in sample size.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Second, this study confirms that stigma has a significant positive impact on loneliness, with interpersonal sensitivity playing a partial mediating role between the two. Finally, we find that resilience plays a moderating In this study, the stigma of young and middle-aged stroke survivors was higher than that of participants in the study by Zheng et al (2023). This may attributed to differences in sample size.…”
Section: Discussionmentioning
confidence: 50%
“…Especially in domestic Chinese society, which is influenced by Confucianism and traditional concepts of face, the stigma experienced during illness may be higher. Related research shows the stigma among young and middle-aged patients experience moderate amounts of stigma (Zheng et al, 2023). Empirical research by Tülay Yildirim found that the emergence of stigma may lead to loss of social identity, reduced social activity, reluctance to seek help from social resources and avoidance behaviours, thereby increasing individual loneliness (Yildirim & Kavak Budak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly so if we depart from a social recognition perspective, where an initial impairment is less visible and obvious, and therefore potentially mis-recognised as a constraint and personal challenge in the public sphere. This is also personal challenges that has been described in previous studies in other minor groups, including minor stroke [24], chronic fatigue [25] and pain [26].…”
Section: Discussionmentioning
confidence: 72%
“…A score of 100 indicates no dependence, 61-99 indicates mild dependence, 41-60 indicates moderate dependence, and 40 or less indicates severe dependence. The Chinese version of the BI has been widely used in stroke survivors (Tian et al, 2023;Zheng et al, 2023). The reliability coefficient was above 0.92, and the split-half reliability coefficient ranged from 0.86 to 0.89, showing good reliability (Cai et al, 2007).…”
Section: Part Twomentioning
confidence: 99%